Employment effects of the new German minimum wage: Evidence from establishment-level micro data - Mario Bossler; Hans-Dieter Gerner (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2016)
In Germany a new statutory minimum wage of exteuro 8.50 per hour of work was introduced on 1 January 2015. We identify employment effects using variation in the establishment-level affectedness. The data allow us to address anticipatory wage adjustments as well as spillover effects within and across workplaces. Difference-indifferences estimation reveals an increase in average wages by 4.8 percent and an employment reduction by about 1.9 percent in affected establishments. These estimates imply an employment elasticity with respect to wages of about -0.3. Looking at the associated labor flows, the employment effect seems mostly driven by a reduction in hires but also by a small increase in separations. Moreover, the employment neutral turnover rate decreases. When analyzing alternative adjustment margins, we observe a reduction in the typical contracted working hours but no effects on freelance employment. – – Am 1. Januar 2015 wurde in Deutschland der allgemeine gesetzliche Mindestlohn eingeführt. Wir identifizieren Beschäftigungseffekte des Mindestlohns durch Variation in der Betroffenheit von Betrieben. Das IAB-Betriebspanel ermöglicht uns dabei, antizipierende Lohnanpassungen und Spill-Over-Effekte zu analysieren. Schätzungen mit der Differenzen-in-Differenzen-Methode zeigen bei betroffenen Betrieben einen Anstieg der durchschnittlichen Löhne um 4,8 Prozent und einen Beschäftigungsrückgang um 1,9 Prozent. Auf die Gesamtbeschäftigung bezogen entspricht das 0,18 Prozent. Der Beschäftigungseffekt ist hauptsächlich auf eine Zurückhaltung in den Einstellungen zurückzuführen. Hochgerechnet hätten ohne den Mindestlohn 60.000 zusätzliche Jobs entstehen können (darin enthalten sind Minijobs und sozialversicherungspflichtige Beschäftigung). Zusätzliche Analysen zeigen einen Rückgang in der beschäftigungsneutralen Beschäftigtenfluktuation. Die Betrachtung weiterer betrieblicher Anpassungsdimensionen zeigt einen leichten Rückgang in den typischen vertraglichen Vollzeitarbeitsstunden, jedoch keinen Anstieg im Einsatz freiberuflicher Beschäftigung.
Keywords: C23; J23; J38; 330; minimum wage; employment; turnover; evaluation; difference-indifferences; Germany